Function and Potential ceRNA Identification of Circ_009773 in Neodymium Oxide Nanoparticle-Induced Lung Epithelial Mesenchymal Transition - Lei Gao; Juan Juan; Zimeng Zheng; Lihua Huang (Toxics)
Nanoparticles of neodymium oxide (NPs-Nd2O3) can induce respiratory-related diseases, including lung tissue injury when entering the organism through the respiratory tract. However, it is currently unclear whether they can induce epithelial–mesenchymal transition (EMT) in lung tissue and the related mechanisms. In this study, we investigated the function of circ_009773 in the process of EMT induced by NPs-Nd2O3 in lung tissue from in vivo as well as in vitro experiments. The findings showed that NPs-Nd2O3 induced EMT in 16HBE cells and SD rat lung tissues. This was characterised by a decrease in epithelial markers and an increase in mesenchymal markers. Additionally, circ_009773 expression was found to decrease in 16HBE cells infected with NPs-Nd2O3 and also decreased in the lung tissues of SD rats. Relevant experiments showed that circ_009773 inhibited EMT in NPs-Nd2O3-treated 16HBE cells and SD rat lung tissues. The previous experiments revealed that circ_009773 was localised in the cytoplasm and functioned at the post-transcriptional level. With the EMT-related pathway used as the basis for circ_009773-related competing endogenous (ce)RNA mechanisms, our observations indicate that circ_009773 is capable of binding to and regulating the expression of miR-135b-5p. In summary, we found that circ_009773 inhibits the EMT induced by NPs-Nd2O3 in lung tissues, and this process likely occurs through competitive binding to miR-135b-5p.